2007
DOI: 10.1002/adfm.200600961
|View full text |Cite
|
Sign up to set email alerts
|

The Large Electrochemical Capacitance of Microporous Doped Carbon Obtained by Using a Zeolite Template

Abstract: A novel microporous templated carbon material doped with nitrogen is synthesized by using a two‐step nanocasting process using acrylonitrile (AN) and propylene as precursors, and Na–Y zeolite as a scaffold. Liquid‐phase impregnation and in situ polymerization of the nitrogenated precursor inside the nanochannels of the inorganic scaffold, followed by gas‐phase impregnation with propylene, enables pore‐size control and functionality tuning of the resulting carbon material. The material thereby obtained has a na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
306
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 497 publications
(315 citation statements)
references
References 51 publications
9
306
0
Order By: Relevance
“…[29][30][31] Specifically, microporous carbons are ideal materials for the electrochemical double-layered capacitors that has been considered as a promising high power energy sources. [32,33] Therefore, as a typical example in the present work, Py-CPN3 was explored as electrodes applied in a EDLC www.afm-journal.de device and compared to commercial available CNTs.…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31] Specifically, microporous carbons are ideal materials for the electrochemical double-layered capacitors that has been considered as a promising high power energy sources. [32,33] Therefore, as a typical example in the present work, Py-CPN3 was explored as electrodes applied in a EDLC www.afm-journal.de device and compared to commercial available CNTs.…”
Section: Resultsmentioning
confidence: 99%
“…We think that most of such oxygen functionalization was introduced into the framework during etching process, as is a case for most carbons derived via the nanocasting method. 20,28,46,52,53 In addition, a small part of oxygen atoms can also result from the moisture, atmospheric oxygen or CO 2 adsorbed on the surface of carbons. All the results declared above underline the importance in producing a replication structure with a high level of zeolite-like orderings, ensuring large surface areas and high pore volumes and therefore resulting in a large storage capacity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Some studies have reported that pore sizes of either 0.4 or 0.7 nm could be suitable for aqueous electrolytes, while a pore size of around 0.8 nm might be better for organic electrolytes. 84,86 In recent papers, 1,105 the match between pore size and ion size was demonstrated through achieving a maximum capacitance.…”
Section: Carbon Materialsmentioning
confidence: 99%